Saltmarsh's essential guide to food additives - Saltmarsh, Michael (Royal Society of Chemistry, 2021)
Providing an invaluable resource for food and drink manufacturers, this book is the only work covering in detail every additive, its sources and uses.
Previous edition: published as Essential guide to food additives. 2013.
Includes index.
Keywords: Food additives.; Food additives -- Law and legislation -- European Union countries.; elektronické knihy; electronic books